Effect of convection gas on the synthesis of nanophase tin oxides during a gas condensation method - Ahn, JP; Park, JK; Kim, BK; Huh, HY (KOREAN INST METALS MATERIALS, 1997)
Tin oxide powders of nanometer size have been synthesized by a gas condensation method using helium or a mixture of oxygen and helium as the convection gas. Changes in the average size, morphology, and crystal phases were investigated during heat treatment at temperatures between 350 degrees C and 720 degrees C in the air. Spherical tin oxide powders of 15 nm in average diameter were synthesized in a helium atmosphere, which was composed of Sn, SnO, and Sn2O3 phases. After annealing at 720 degrees C, these multiphase particles transformed to a single SnO2 phase and became an irregular shape of about 50 nm in diameter. This rapid coarsening was attributed to fast mass transfer among particles. The spherical SnO2 powder of 7 nm in average diameter was directly synthesized using a gas mixture of oxygen and helium. Upon annealing up to 720 degrees C, morphological changes were barely observed in the powder synthesized using a convection atmosphere containing oxygen.
Keywords: DIPHASIC XEROGELS; NANOCRYSTALLINE